2008
DOI: 10.1099/jmm.0.2008/001636-0
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of gatifloxacin with cefoperazone and cefoperazone–sulbactam against resistant strains of Pseudomonas aeruginosa

Abstract: Chequerboard and time-kill methods were used to compare the in vitro efficacies of the combinations gatifloxacin (GAT) with cefoperazone (CFP) and GAT with cefoperazonesulbactam (CFP-SUL) against 58 clinical isolates of Pseudomonas aeruginosa. The combinations GAT+CFP and GAT+CFP-SUL were shown to be synergistic for 36.2 and 58.6 % of isolates tested, respectively, using the chequerboard method. Time-kill studies with 11 strains showed synergy in 54.5 % for the GAT+CFP combination and 72.7 % for the GAT+CFP-SU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Other authors have reported agreement between 72-81 per cent. 24 The results of this study demonstrate that the combination of piperacillintazobactam and levofloxacin achieve in-vitro synergy in 72.7 per cent of P. aeruginosa isolates. In contrast, levofloxacin and cefoperazone-sulbactam combination was synergistic in just 30 per cent of the tested isolates.…”
Section: Discussionmentioning
confidence: 65%
“…Other authors have reported agreement between 72-81 per cent. 24 The results of this study demonstrate that the combination of piperacillintazobactam and levofloxacin achieve in-vitro synergy in 72.7 per cent of P. aeruginosa isolates. In contrast, levofloxacin and cefoperazone-sulbactam combination was synergistic in just 30 per cent of the tested isolates.…”
Section: Discussionmentioning
confidence: 65%
“…Drug combinations of antimicrobial agents belonging to different antibiotic classes is an approach broadly used in the clinical practice to fight antibiotic-resistant bacterial infections. FQs are commonly combined with β-lactams (as cephalosporins and/or carbapenems) or antifungal agents due to their known synergistic effect [ 115 , 116 , 117 , 118 , 119 , 120 ]. Although FQs do not have antifungal activity, their ability to bind to topoisomerase of fungi may explain the synergistic activity resulting from their combination with some antifungal agents [ 119 ].…”
Section: Antimicrobial Activity Mechanism Of Action and Safety Profile Of Metalloantibioticsmentioning
confidence: 99%